Tensile Resistance of GFRP Wrapped Steel-Dowelled Half-Lap Timber Connection - Ali Chew, Amirah; Atikah Seri, Nurul; Nur Syazni Wan Shaari, Wan; Hanafie Yasin, Mohd; Hassan, Rohana (International Journal of Engineering and Technology, 2018)
Generally, the use of timber mainly focuses on simple structures or structures that can take small loads. This paper report on tensile resistance of steel dowelled timber connection wrapped with glass fibre reinforced polymer (GFRP). It involved experimental work in laboratory designed to determine the tensile strength behaviour for half-lap timber connections with steel dowel as the mechanical    fasteners. Bintangor species representing strength group 5 and Yellow Meranti species representing strength group 6 were tested in the conditions of with and without the GFRP wrapping. The performances of the connections were observed using the European Yield Model (EYM) as the guideline. The EYM theory is generally used to determine the load carrying capacity of timber-to-timber, panel-to-timber and steel-to-timber connections, reflecting all possible modes of failures. All half-lap connection members were tested at the rate     0.0006 mm/min using the universal testing machine. As a result, it was found that the steel-dowelled half-lap timber connection with GFRP wrapping performed better than the timber connection without the wrapping. The ultimate load of GFRP wrapped connections made of Bintangor and Yellow Meranti species were found increased at 17% and 44% higher compared to the connection without the GFRP wrapping accordingly.